2020
DOI: 10.1186/s12876-020-01337-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of albumin infusion on the risk of rebleeding and in-hospital mortality in cirrhotic patients admitted for acute gastrointestinal bleeding: a retrospective study of a single institute

Abstract: Background: To investigate the effect of albumin infusion on cirrhotic patients admitted for acute gastrointestinal bleeding. Methods: Medical records of cirrhotic patients who admitted due to acute gastrointestinal bleeding through January 2009 to December 2018 were reviewed. Clinical data and the total amount of albumin and red blood cell used during hospitalization were recorded. For patients with rebleeding, the amount of albumin and red blood cell used before rebleeding was also documented. The primary ou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Hypoalbuminemia is considered an indicator of the severity of liver dysfunction 33 . Wang et al 34 found that albumin infusion can reduce the risk of recurrent bleeding and hospital death in patients with cirrhosis and EGVB. Univariate analysis in this study suggested that albumin was a protective factor for recurrent bleeding (0.895).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoalbuminemia is considered an indicator of the severity of liver dysfunction 33 . Wang et al 34 found that albumin infusion can reduce the risk of recurrent bleeding and hospital death in patients with cirrhosis and EGVB. Univariate analysis in this study suggested that albumin was a protective factor for recurrent bleeding (0.895).…”
Section: Discussionmentioning
confidence: 99%
“… 43 This probably is due to improved hemodynamics and GFR, especially in those achieving higher serum albumin (4g/dl) as shown in the post hoc analysis. Our choice of targeting serum albumin level to 4 g/dl was based on previous experience in our unit where in-patients having a serum albumin level at or above 4 g/dl had better survival (unpublished observation), a fact supported by post hoc analysis of ANSWER trial and by Wang et al 44 Similar to our study, Terlipressin with albumin was reported to be better in reversing HRS, as compared to Placebo with albumin, with a presumed beneficial effect in reducing portal pressure and consequently decreased gut congestion, endotoxemia, and reduced pro-inflammatory cytokines. 45 The merit of our study is that we have demonstrated the benefit of response-guided SAFI±T/NAdr therapy on survival through improved hemodynamics, cytokines, and Netosis ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al [32]conducted a multicenter retrospective study and found that the albumin concentration > 31.5 g/L was a protective factor for early rebleeding after EVL. A retrospective study by Wang et al [33]showed that in patients with hypoalbuminemia, albumin infusion can reduce the risk of in-hospital rebleeding, and in patients with Child-Pugh class C, albumin infusion can reduce the number of in-hospital deaths. The results in this study also showed that rebleeding after EVL may be related to a low albumin level.…”
Section: Construction Of the Nomogram Prediction Modelmentioning
confidence: 99%